Hajj vaccination strategies: Preparedness for risk mitigation - Majid Alshamrani; Fayssal Farahat; Mohammed Alzunitan; Musallam Abu Hasan; Nisreen Alsherbini; Ali Albarrak; Sameera M Al Johani; Atef shibl; Jaffar A. Al-Tawfiq; Alimuddin Zumla; Ziad A. Memish (Journal of Infection and Public Health)
Millions of pilgrims travel annually to Makkah and Madinah, Saudi Arabia, for the Hajj, posing unique challenges for public health management and disease control. The large influx of pilgrims from diverse backgrounds traveling to a confined geographic area, coupled with the close proximity and interactions among them, create significant pressure on the healthcare system and heighten the potential for the spread of communicable diseases. This review examines current trends in communicable diseases and their impact, drawing insights from expert perspectives on the required (i.e., meningococcal meningitis, polio, and yellow fever) and recommended vaccinations (influenza, COVID-19) for Hajj participants. The updated COVID-19 vaccine is mandatory for local pilgrims and is strongly recommended for international visitors, with ongoing discussions on adapting protocols to address emerging variants. The timing and strain coverage of influenza vaccination, along with quadrivalent meningococcal vaccination, are also emphasized as critical preventive measures. Diseases such as cholera and yellow fever are addressed underscoring the need for rigorous surveillance and targeted vaccination strategies to mitigate the risk of transmission during the Hajj. By providing up-to-date information on mandated and recommended vaccinations, this review aims to empower pilgrims and healthcare professionals to make informed decisions regarding public health and disease prevention during this significant event.